2015
DOI: 10.1021/acs.jpcc.5b03819
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Absorption in Graphene Enhanced by the Excitonic Fano Resonance

Abstract: We report our observation of two-photon absorption (2PA) in graphene enhanced by the excitonic Fano resonance at the saddle point with femtosecond laser pulses in the spectral range from 1.8 to 2.9 eV (or, from 435 to 700 nm). On the basis of the second-order, time-dependent perturbation theory on interband transitions among three states near the saddle point of two-dimensional systems (used in the Bassani−Hassan theoretical model), we develop a semiempirical model to take excitons in graphene into considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The measured saturation intensity is low when compared to the reported values in various spectral ranges, especially at visible range [47][48][49][50][51][52][53][54]. However, it is comparable with the theoretical value [55].…”
Section: Nonlinear Optical Characterizationsupporting
confidence: 55%
“…The measured saturation intensity is low when compared to the reported values in various spectral ranges, especially at visible range [47][48][49][50][51][52][53][54]. However, it is comparable with the theoretical value [55].…”
Section: Nonlinear Optical Characterizationsupporting
confidence: 55%
“…This was less than two orders of magnitude lower than measurements from a high quality, transferred, few-layer graphene (5-7 layers) [8], was comparable to that of graphene dispersions, [41] and was about six orders of magnitude higher than that of common dielectrics. Furthermore, the obtained I sat value from GrPPF was one order of magnitude higher than that of few-and multilayer graphene (which have thickness less than 10 nm) [8,42]. In [42], it was shown that I sat is directly proportional to the number of graphene layers.…”
Section: Discussionmentioning
confidence: 90%
“…The measured saturation intensities, I s , and saturation fluences, F s , are presented in Figure 6 as functions of photon energy, E ph (See Supporting Information for the listed values), and compared with measurements published in literature. 2,5,9,[17][18][19]38,39 In each case, graphene sheets were produced by either mechanical exfoliation, epitaxy, or CVD and the direction of incident radiation was perpendicular to the graphene plane. Cases for graphene flakes suspended in a solution or polymer were excluded from the analysis because the angle of incidence is not uniform and the incident beam is more likely to interact with flake edges where disorder is high.…”
Section: Resultsmentioning
confidence: 99%
“…Two-photon absorption (2PA) has been observed in the spectral region between 435 nm and 1100 nm (1.1 eV to 2.9 eV). 18,19 The strength of 2PA is greater in stacked layers than single layer graphene due to the increased number of energy bands caused by interlayer coupling and thus a greater number of possible electronic transitions. 18 The effective modulation depth of graphene is limited by 2PA which can be detrimental to passive mode-locking.…”
Section: Introductionmentioning
confidence: 99%